2017
DOI: 10.5505/turkhijyen.2016.24650
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanisms of the effect of anticancer activity on lichen metabolites

Abstract: The components obtained from natural products Makale Dili "Türkçe"/Article Language "Turkish"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In recent studies, it has been shown that the number of lichens reaches 1000 and many metabolites that are specific to lichens are synthesized by these lichen species (Özenoğlu et al, 2013). In the literature, these lichen metabolites have been reported with their antibiotics, antimycotic, antiviral, anti-inflammatory, analgesic, antipyretic, antiproliferative and cytotoxic effects (Rankovic et al 2007;Şekerli et al, 2017). Studies in our country on antimicrobial activities of lichens are quite insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, it has been shown that the number of lichens reaches 1000 and many metabolites that are specific to lichens are synthesized by these lichen species (Özenoğlu et al, 2013). In the literature, these lichen metabolites have been reported with their antibiotics, antimycotic, antiviral, anti-inflammatory, analgesic, antipyretic, antiproliferative and cytotoxic effects (Rankovic et al 2007;Şekerli et al, 2017). Studies in our country on antimicrobial activities of lichens are quite insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] As a result of these studies, lichen secondary metabolites may provide important results related withits use as candidate drug molecules. Usnic acid and its enantiomers are the most extensively studied lichen secondary metabolites.…”
mentioning
confidence: 99%